Impact of angle cap and water-filled blade modification on the output of overshot waterwheels - Afandi, Rizki Afif; Mugisidi, Dan; Parwatmoko, Giri; Heriyani, Oktarina (Jurnal Polimesin, 2025)
The utilization of water resources as renewable energy through waterwheels presents an environmentally friendly alternative, however, its efficiency requires improvement through technological modification. This research investigates two design modifications: a 45° Angle Cap (AC) and a Water-Filled Angle Cap (WFAC), in comparison with a waterwheel without a Cap (WC). Experiments were conducted at discharges from 1 to 10 m³/h with a constant torque load of 0.05 N-m. The highest efficiency of 57.08% was achieved in the AC 45° configuration at 1 m³/h, generating 1.09 watts of power, while the WFAC 45° yielded the highest power output of 2.88 watts at 10 m³/h with an efficiency of 14.50%. Although increasing discharge generally led to higher power input, it was accompanied by a decrease in efficiency across all configurations. Among all three variations, WFAC 45° demonstrated superior performance at higher discharges, indicating its potential for enhancing the power and efficiency of overshot waterwheels.